2007
DOI: 10.1126/science.1138071
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Versus Bottom-Up Control of Attention in the Prefrontal and Posterior Parietal Cortices

Abstract: Attention can be focused volitionally by “top-down” signals derived from task demands and automatically by “bottom-up” signals from salient stimuli. The frontal and parietal cortices are involved, but their neural activity has not been directly compared. Therefore, we recorded from them simultaneously in monkeys. Prefrontal neurons reflected the target location first during top-down attention, whereas parietal neurons signaled it earlier during bottom-up attention. Synchrony between frontal and parietal areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

197
1,715
11
18

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,118 publications
(1,941 citation statements)
references
References 28 publications
197
1,715
11
18
Order By: Relevance
“…3b). The observation that mid-and high-gamma activity were related to the phase consistency of beta and theta activity, respectively, extends the ideas that gamma frequency variations reflect information routing 32,34,45,46 and that message-passing is indexed by specific hierarchical combinations of slow and high frequencies (low/high frequency ratio) 47 .The current data demonstrate that violating intermodal expectations changes the neural dynamics of slow (delta and theta) brain activity, and increases the coordination between local low-beta and high-gamma oscillatory activity. Our data suggest that this transition occurs in brain regions where audio-visual predictions are likely updated (STS) and new prediction errors generated (auditory and visual cortices).…”
supporting
confidence: 70%
“…3b). The observation that mid-and high-gamma activity were related to the phase consistency of beta and theta activity, respectively, extends the ideas that gamma frequency variations reflect information routing 32,34,45,46 and that message-passing is indexed by specific hierarchical combinations of slow and high frequencies (low/high frequency ratio) 47 .The current data demonstrate that violating intermodal expectations changes the neural dynamics of slow (delta and theta) brain activity, and increases the coordination between local low-beta and high-gamma oscillatory activity. Our data suggest that this transition occurs in brain regions where audio-visual predictions are likely updated (STS) and new prediction errors generated (auditory and visual cortices).…”
supporting
confidence: 70%
“…The power of gamma activity is increased during cognitive processes [Corbetta and Shulman, 2002]. Previous studies have reported associations between attention and gamma frequency synchronization to integrate neural assemblies associated with a specific sensory object [Jensen et al, 2007], and gamma band changes have been reported across the visual cortex, frontal eye fields, SPL, and dorsal lateral prefrontal cortex [Buschman and Miller, 2007; Ossandon et al, 2012]. The decreased power in low‐frequency bands and increased power in high‐frequency bands in this study is compatible with these findings and shows that common brain areas were actively involved during the two tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Hipp et al (2011) have identified large scale beta synchronization in a distinctive network of frontal, parietal and extrastriate visual areas in relation to visual perceptual organization. Fronto-parietal synchrony in the beta band also has been associated with visual search (Buschman and Miller, 2007), integration of visual information and perceptual grouping (Srinivasan et al, 1999;Phillips and Takeda, 2009;Phillips et al, 2012;Volberg and Greenlee, 2014;Castellano et al, 2014), visual attention (Gross et al, 2004;Marois et al, 2000;Wróbel, 2000), and visual object recognition (Sehatpour et al, 2008;Castellano et al, 2014). These previous studies, however, point to the existence of ongoing fronto-parietal beta synchronization that modulates brain responses to visual input (Gross et al, 2004;Liang et al 2002;Hipp et al, 2011), or beta synchrony at later stages (150-300 ms) of visual stimulus processing (Phillips et al, 2012;Sehatpour et al, 2008;Dehaene and Changeux, 2011).…”
Section: Fronto-parietal Beta Synchronization During Visual Processingmentioning
confidence: 98%